Cake Application as a Tool for Boosting Vocabulary Mastery in EFL Education - Nabilla Dwi Hardiana; Yani Lubis (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research assessed the efficacy of the Cake application in enhancing English vocabulary proficiency among 8th-grade students at SMP IT Daarul Istiqlal Marindal I. In the present epoch of globalization, mastery of the English language has become indispensable, and digital platforms such as Cake provide inventive methods to facilitate interactive and pleasurable vocabulary acquisition. This study used a quantitative methodology, using a one-group pre-test and post-test design. The research included a sample of 30 students that were carefully chosen. The data was gathered via a preliminary assessment to gauge the level of vocabulary proficiency before using the Cake application. This study investigates whether the Cake application significantly enhances vocabulary proficiency among 8th-grade EFL students. This was followed by a period of application use, and subsequently, a post-assessment was conducted to assess the enhancement in vocabulary mastery after utilizing the program. The data analysis was performed using SPSS 25, which included doing normality tests, descriptive statistical analysis, and paired T-tests. The research results indicated a significant improvement in students' proficiency in vocabulary after the use of the Cake program, as shown by a mean pre-test score of 53.67 and a post-test score of 76.00. The paired T-test confirmed this disparity with a significance value of 0.000, suggesting that the enhancement in students' learning outcomes was not a result of chance. The study's findings indicate that using the Cake application is a successful method for enhancing pupils' proficiency in English vocabulary. This program not only improves vocabulary abilities, but also stimulates students' enthusiasm for studying English with its captivating interactive elements. Hence, it is advisable for educators to contemplate using digital tools such as Cake to boost vocabulary acquisition inside the classroom setting.